Implementation Teaching at the Right Level (TaRL) Approach Based Flipped Card Game on Learning Outcomes of Football Dribbling Skills - Alfi Wahyudi; Reshandi Nugraha; Marisa Noviyanti Fajrah Ilsya (JUMORA: Jurnal Moderasi Olahraga, 2024)
This study investigates the effectiveness of the Teaching at the Right Level (TaRL) approach combined with flipped card games in enhancing football dribbling skills among eighth-grade students at SMPN 1 Ciparay (class VIII C). Using a Classroom Action Research (CAR) design, the research was conducted over two cycles, each comprising two sessions. The study involved 45 students, with their learning outcomes evaluated based on the Minimum Mastery Criterion (MMC) set at 75. Data collection methods included observation sheets and learning outcome tests. This descriptive quantitative approach analyzed the percentage of students achieving the MMC. The findings revealed a significant improvement in mastery levels. In the first cycle, 34 students (75.56%) met the MMC, increasing to 39 students (86.67%) in the second cycle. Meanwhile, the number of students who did not meet the MMC decreased from 11 students (24.44%) in the first cycle to 6 students (13.33%) in the second cycle. These results demonstrate the success of integrating the TaRL approach with flipped card games in improving student learning outcomes. As such, this method presents an effective alternative teaching strategy for enhancing dribbling skills in football learning activities